(untitled) (Tempo e Argumento, 2010)
This text has four parts. 1) First it focuses on the concept of testimony, analyzing its etymology and meaning as a special category that implies a singular relation with the “real”. 2) It also discusses the relationship between the testimony and others modalities of the writing in first person with emphasis on the concepts of diary and autobiography. 3) After that, the text presents the political meaning of the testimony, that works as a means of construction of a memory against the oblivion as well as a “work of memory” concerning social traumas. 4) The last section is dedicated to the study of the singular position of Brazil as a country in Latin America that has not been able to create a political and cultural space for the memory of the 1964-1985 dictatorship. This article resumes the paper presented at the “I Congresso Internacional da Cátedra Jorge de Sena - Andanças Prodigiosas da Literatura”, that took place at the Faculdade de Letras of the Universidade Federal do Rio de Janeiro, in October 2009, and it includes as well in some moments parts of other already published articles.